A new station for optical observation of electron beam parameters at electron storage ring SIBERIA-2. (20th December 2016) - Meshkov, O.; Stirin, A.; Kovachev, G.; Korchuganov, V.; Odintsov, D.; Tarasov, Yu.; Valentinov, A.; Zabelin, A.; Borin, V.; Dorokhov, V.; Khilchenko, A.; Kvashnin, A.; et al.
Abstract: A new station for optical observation of electron beam parameters at the electron storage ring SIBERIA-2 is dedicated for measurement of the transverse and longitudinal size of electron bunches with the use of the synchrotron radiation (SR) visible spectrum in single-bunch and multi-bunch modes and for study of time-dependent behavior of individual electron bunches with changing accelerator parameters. The article briefly describes the main components of the diagnostics and the experimental results.